Bimetallic MOFs (H3O)x[Cu(MF6)(pyrazine)2]·(4 - x)H2O (M = V^4+, x = 0; M = Ga^3+, x = 1): co-existence of ordered and disordered quantum spins in the V^4+ system. - Manson, J; Schlueter, J; Garrett, K; Goddard, P; Lancaster, T; Möller, J; Blundell, S; Steele, A; Franke, I; Pratt, F; Singleton, J; Bendix, J; et al. (Royal Society of Chemistry, 2016)
The title compounds are bimetallic MOFs containing [Cu(pyz)2]^2+ square lattices linked by MF6^n- octahedra. In each, only the Cu^2+ spins exhibit long-range magnetic order below 3.5 K (M = V^4+) and 2.6 K (M = Ga^3+). The V^4+ spins remain disordered down to 0.5 K.